Effects of Geographic Inquiry Process and Virtual Learning Techniques on Spatial Thinking Ability of Upper Secondary Students - Harachai, Pitchapa; Lertdechapat, Kornkanok (An Online Journal of Education, 2024)
This research studied the effects of teaching through the geographic inquiry process using virtual learning techniques on the spatial thinking ability of high school students. The research objectives were: 1) to compare the spatial thinking ability of students before and after learning through the geographic inquiry process combined with virtual learning techniques; and 2) to study changes in students’ spatial thinking ability regarding each component: 1) Concepts of space 2) Using tools of representation 3) Processes of reasoning before and after this treatment. The sample group was 38 students of Mathayom-5 from a school in Bangkok who studied Social Studies and Geography in the first semester of academic year 2024. The participants were selected via purposive sampling and the study used a pre-experimental research method. The instruments used were a spatial thinking ability test, a teaching plan utilizing the geographic inquiry process combined with virtual learning techniques, and a post-activity record. Data were analyzed using statistics such as arithmetic mean, standard deviation, and t-test, as well as content analysis. The results of the research found that: 1) students had significantly higher spatial thinking capabilities after learning through this method than before at the .05 level of significance, and 2) students who learned through this process improved both overall and in terms of each component.